INDIVIDUAL, ABSOLUTE AND RELATIVE CARDIOVASCULAR RISK IN ELDERLY PATIENTS WITH ARTERIAL HYPERTENSION AND ITS DYNAMICS UNDER ANTIHYPERTENSIVE TREATMENT - B. A. Hapayev; L. I. Olbinskaya (Российский кардиологический журнал, 2001)
We have estimated the 10-year absolute (AR) and relative (RR) cardiovascular risk in 30 patients (12 men and 18 women, mean age 55,5±7,2 years with essential hypertension, mild to severe (WHO/ISH, 1999) with the usage of a computer program dealing with the contribution of various risk factors in the Framingham study. The AR calculated from SBP/DBP, equaled 15.4/17.8%, decreasing to 9.8/10.9% after 6 months of Nebivolol treatment (p<0,001), whereas the standard AR for the same age and sex made 5.4/6.7%. The RR, calculated from SBP/DBP ОР, equaled 249/208%, decreasing to 98/65% after 6 months of treatment (p<0,001) with the target level recommended for hypertensive patients (<20%) achieved in 23,3/53,3%. Decreases in AR and RR was not just due to a BP decrease but also the influence of treatment on LVH, absent dynamics of blood lipid and carbohydrate levels, and in smokers – the effect of quitting.